Transgenic Plants Methods and Protocols - Dunwell, Jim M.; Dunwell, Jim M.; Wetten, Andy C.; Wetten, Andy C. (Methods in Molecular Biology, 2012)
In 2010 the global area of transgenic crops reached 148 million hectares, an 87-fold increase since 1996, making it the most rapidly adopted technology in the history of modern agriculture. In Transgenic Plants: Methods and Protocols, Second Edition expert researchers in the field provide key techniques to investigate production and analysis of transgenic plants.  Focusing on selection and detection methods, transformation technology, gene targeting, silencing and directed mutation, metabolic engineering and pharming, the book encompasses protocols relating to major crops and model plants being used for genomic analysis. Written in the highly successful Methods in Molecular Biology™ series format, the chapters include the kind of detailed description and implementation advice that is crucial for getting optimal results in the laboratory.   Thorough and intuitive, Transgenic Plants: Methods and Protocols, Second Edition aids scientists in the continuous improvements being made for the production and analysis of transgenic plants.